2002
DOI: 10.1038/sj.mp.4001146
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of structural polymorphisms and C-1018G promoter variant of the 5-HT1A receptor gene as putative risk factors in major depression

Abstract: Scientific Correspondence 930Molecular Psychiatry with PD ( 2 = 5.14, 1 df, 2 P = 0.02), suggesting a tendency to heterozygosity in PD (Table 1).To date, most of the efforts to elucidate the genetic factors underlying PD have been focused on genes whose products are involved in its pathophysiology or that could mediate the biological effects caused by panicogenic agents. Changes in the expression or function of NTRK3 may alter synaptic plasticity through the change of local trophic support. This could possibly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 10 publications
2
25
2
1
Order By: Relevance
“…8 The À1019G allele or the homozygous À1019GG genotype has been associated with depression, suicide, bipolar disorder, panic disorder with agoraphobia, neuroticism and decreased antidepressant response. [8][9][10][11][12][13][14][15] We tested the hypothesis that the HTR1A À1019G allele increases depression risk in a Utah population. Observed frequencies of À1019G allele (350/688) and À1019GG genotype (89/344) were 1.10-and 1.34-fold higher among unrelated individuals affected with MDD compared to unaffected individuals (312/672 and 65/336; one-tailed Fisher's exact test P = 0.05 and 0.02, respectively).…”
Section: Serotonin Receptor 1a-conditional Genetic Analysismentioning
confidence: 99%
“…8 The À1019G allele or the homozygous À1019GG genotype has been associated with depression, suicide, bipolar disorder, panic disorder with agoraphobia, neuroticism and decreased antidepressant response. [8][9][10][11][12][13][14][15] We tested the hypothesis that the HTR1A À1019G allele increases depression risk in a Utah population. Observed frequencies of À1019G allele (350/688) and À1019GG genotype (89/344) were 1.10-and 1.34-fold higher among unrelated individuals affected with MDD compared to unaffected individuals (312/672 and 65/336; one-tailed Fisher's exact test P = 0.05 and 0.02, respectively).…”
Section: Serotonin Receptor 1a-conditional Genetic Analysismentioning
confidence: 99%
“…The heterogeneity may result from (1) different ancestries (Asian population versus Caucasian population), (2) incomplete genotyping rates or genotyping error rates in different studies. Although the studies by Arias et al 16 and Koks et al 18 reported that the major allele was 'G' , other studies showed that the major allele was 'C' . We contacted the corresponding authors with regard to the genotype data in these studies.…”
Section: Discussionmentioning
confidence: 81%
“…In the meta-analysis, seven population-based association studies, including this study, met our criteria for rs6295 4,6,[16][17][18][19] (Table 2). We found significant heterogeneity among ORs (Q¼16.2, df¼6, P(Q)¼0.0119).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, 5-HT selective reuptake inhibitors (SSRI), which increase serotonergic tone, are first-line anxiolytic and antidepressant treatments (Ballenger, 1999;Kugaya et al, 2003). A genetic variant that reduces expression of 5-HT transporter has been associated with elevated levels of anxiety-like traits, susceptibility to affective disorder, and depressive symptoms (Arias et al, 2002;Collier et al, 1996;Lesch et al, 1996). These findings suggest that in utero exposure to DEPs could affect 5-HT transporter function in the DRN of male offspring, providing a possible mechanism underlying the increase in anxiety-like behavior.…”
Section: Discussionmentioning
confidence: 99%